Tradução e adaptação cultural da versão brasileira da Four Habits Coding Scheme (4HCS) para ensino e avaliação das habilidades de comunicação de profissionais de saúde - Catani, Renata Rodrigues (2017)
Objective: To translate and culturally adapt, into Brazilian Portuguese, the Four Habits Coding Scheme (4HCS), an instrument for teaching and assessing clinicians’ communication skills in a person-centered care approach. Methods: The translation process was accomplished in seven stages: initial translation, reconciliation, back translation, review by the author, independent review, consensus version through Dephi technique, review by a language coordinator, and pre-test. During pre-test, three independent observers assessed four medical consultations performed by medical students and residents that had been recorded in a real health care scenario. Results: Reviewers had difficulty in reaching consensus on expressions referring to understanding the whole person, such as "Engage in small talk”, "Expansion of concerns”, "Elicit full agenda”, "Use patient’s frame of reference”, and "Explore plan acceptability”. They also had difficulty in reaching consensus on the translation of the word "clinician”, which was first translated as "physician”. Historical and cultural issues in the physician- patient relationship may have influenced this result. Conclusions: The Brazilian 4HCS is a culturally, conceptually, semantically and operationally sound instrument. It represents an important advance not only for strengthening the person-centered care model in Brazil, but also for international studies aimed at cross-cultural comparisons of health care models and systems.